Coating durability evaluation method and highly durable coating
By using ultraviolet irradiation in a hydrogen peroxide solution to measure ion concentrations from fluororesin-based coatings, the method addresses the limitations of conventional durability assessments, providing a comprehensive evaluation of internal deterioration and identifying highly durable coatings.
Patent Information
- Application Number
- JP2021101247
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-18
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-06-18
AI Technical Summary
Conventional methods for evaluating the durability of coating films, such as fluororesin-based paints, only assess surface conditions like gloss and color, failing to account for internal deterioration, which can lead to varying protective properties and potential corrosion under the coating.
A method involving ultraviolet irradiation in an aqueous hydrogen peroxide solution is used to accelerate testing, measuring the ion concentration of eluted fluorine and organic ions to evaluate the internal deterioration of the coating film, providing a more comprehensive assessment of durability.
This method allows for the evaluation of long-term durability by assessing internal deterioration, providing a more accurate judgment of coating film performance beyond surface-level measurements, and identifying highly durable fluororesin-based coatings.
Smart Images

Figure 0007654191000005 
Figure 0007654191000006 
Figure 0007654191000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for evaluating the durability of a coating film and to a highly durable coating film. [Background technology]
[0002] There are an increasing number of cases where coating materials used outdoors are required to have long-term durability against ultraviolet degradation and the like. A representative example of a durable coating is a fluororesin-based coating (Non-Patent Document 1) classified as Class 1 Weather Resistant Coating for Steel Structures under JIS K5669. Accelerated tests of the durability of these coatings in outdoor environments have been published, using test equipment such as JIS B7751 "Ultraviolet Carbon Arc Lamp Light Fastness Tester and Weather Resistance Tester" and JIS B7753 "Sunshine Carbon Arc Lamp Light Fastness Tester and Weather Resistance Tester."
[0003] In addition, a test has been published in which hydrogen peroxide is intermittently sprayed, focusing on the photocatalytic activity of pigments used in paints (Non-Patent Document 2). It has been reported that the method using hydrogen peroxide has a good correlation with the deterioration state in real environments as a method for evaluating the topcoat of a highly durable coating film.
[0004] In all of these tests, the test material is irradiated with light including ultraviolet rays in a wet or dry environment, and durability is evaluated based on the appearance of the test material after irradiation and changes in gloss and color due to surface properties.
[0005] Meanwhile, for outdoor power facilities such as power distribution equipment and transmission towers, achromatic heavy-duty anticorrosive paints containing titanium oxide pigments are often used, and as such, studies have been conducted on the oxidative deterioration of coating resins caused by the photocatalytic action of titanium oxide as a major factor affecting the weather resistance of coatings (Non-Patent Document 3).Non-Patent Document 3 also reports that, based on the results of exposure tests in which fluororesin-based paints using pigments with different photocatalytic activities were applied to carbon steel materials, the catalytic activity of titanium oxide pigments affects the gloss retention rate and decomposition of coating resins of the test materials. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] JIS K5659:2018 Weather-resistant paint for steel structures [Non-Patent Document 2] Kanji Mori et al. "Development of a high-speed weather resistance test method for coating films" Journal of Materials Life, 13[4] p180-184 (Oct.2001) [Non-Patent Document 3] Ichiba, Mikiyuki et al., "Study on weather resistance evaluation method of heavy-duty anticorrosive coating film," 57th Materials and Environment Symposium, p334-337 (2010) DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0007] However, when the inventors investigated paint materials that had deteriorated over time, they found that even in fluororesin-based paints classified as Class 1 weather-resistant paints for steel structures according to JIS K5659, the degree of deterioration over time, such as rusting, differed depending on the paint used. In other words, it was found that even if the gloss retention of coating films is the same, the protective properties of the coating film are not the same, and there are coating films that are sound and those where corrosion of the steel material occurs underneath the coating film. It was inferred that the surface gloss of the coating film may be influenced by factors unrelated to the durability performance of the resin, such as the type and shape of the inorganic pigment in the coating film. Therefore, it was suggested that in order to evaluate the durability of a coating film, it is necessary to evaluate not only the surface condition such as the gloss and color of the coating film, but also the deterioration of the inner layer of the coating film. The problem was that the deterioration state inside the coating film could not be judged by measuring only the surface condition such as gloss and color, which has been applied to conventional accelerated test methods and exposure tests.
[0008] In order to solve the above problems, the present invention aims to provide a method for evaluating the durability of a coating film against deterioration over time, including deterioration not only of the surface but also of the inside of the coating film, particularly for a coating film of a fluororesin-based coating film which is generally known as a durable coating film. A further object of the present invention is to provide a highly durable fluororesin coating film by using a method for evaluating the durability of the coating film. [Means for solving the problem]
[0009] The present inventors have used an accelerated test environment of ultraviolet irradiation in an aqueous hydrogen peroxide solution as a method for evaluating the durability of coating films, and have focused on substances eluted from the coating films to obtain information on deterioration inside the coating films, using fluororesin-based coating films and polyurethane resin-based coating films that are generally used in heavy-duty anticorrosive coating systems as the target coating films. That is, in a predetermined amount of aqueous hydrogen peroxide solution, a coating film of a predetermined area was irradiated with light containing ultraviolet rays of a predetermined intensity for a predetermined time, and the ion concentration in the solution after irradiation was measured by ion chromatography, and the durability of the coating film was evaluated using the ion concentration converted per unit area of the coating film (hereinafter referred to as ion concentration per unit area) as an index.
[0010] When the concentration of hydrogen peroxide solution is less than 0.5% by mass, the amount of fluoride ions and organic ions eluted is small even when exposed to light including ultraviolet light, so the ion concentration per unit area is small and the variation is large, but even when the concentration exceeds 1.5% by mass, there is no change in the amount of fluoride ions and organic ions eluted. On the other hand, discoloration was confirmed in the coating film toned with organic pigments.
[0011] In addition, the contact area of the test material with the hydrogen peroxide solution was 0.7 cm 2 Below 12cm, the amount of eluted fluoride ions and organic ions is small and the analytical error becomes large. 2 Above this value, uniform light irradiation becomes difficult, and the ion concentrations per unit area of fluorine ions and organic ions become smaller.
[0012] As a light source, a mercury lamp is preferable because it has a stable output from the ultraviolet region to visible light, and an LED lamp with a wavelength in the range of 280nm to 380nm is also applicable when the irradiation area is small. When the intensity of the irradiation light in the wavelength range of 280nm to 380nm is weak, or when the irradiation light wavelength does not include the range of 280nm to 380nm and is in the visible light range exceeding 380nm, the elution of fluoride ions and organic ions is significantly reduced and evaluation was not possible.
[0013] In addition, the irradiation intensity was specified by the intensity of the wavelength when the light source had a single wavelength, and was specified by the intensity of the wavelength from 300 nm to 400 nm when the light source had a wide wavelength range. 2 Below 90 W / m, the amount of fluoride ions and organic ions dissolved was significantly reduced. 2 Above this time, the amount of fluoride ions and organic ions dissolved increased, but the reproducibility of the amount of dissolved was poor. For irradiation times of less than 6 hours, the amount of fluoride ions and organic ions dissolved decreased significantly, and above 48 hours, the amount of fluoride ions and organic ions dissolved plateaued, and the amount of dissolved relative to the contact area decreased, causing a decrease in reproducibility. It was presumed that decomposition products insoluble in water accumulated on the surface of the coating, inhibiting the deterioration reaction.
[0014] In a 10-year exposure test in a real environment, the gloss retention of all highly durable fluororesin-based coatings decreased (see Table 1 below). For coatings that showed good corrosion protection performance but had a gloss retention rate of less than 50%, unexposed stored materials were immersed in a 1% by mass hydrogen peroxide solution at a liquid temperature of 50°C and an irradiation intensity of 80 W / m 2 After 24 hours of light irradiation, the hydrogen peroxide solution was analyzed for ions, and the fluoride ion concentration was found to be 0.1 ppm / cm 2 It was found that: In other words, the amount of fluorine ions dissolved in the hydrogen peroxide solution correlates with the corrosion prevention performance of the coating film, but the correlation with gloss retention could not be determined solely from the amount of fluorine ions.
[0015] On the other hand, for a coating that also showed a decrease in gloss retention and the same level of remaining film thickness but showed signs of rusting, an ion analysis of an aqueous hydrogen peroxide solution was carried out after light irradiation under the same conditions as above using unexposed stored material. The fluorine ion concentration was 0.1 ppm / cm 2 It was confirmed that the fluoride ion concentration was less than 0.1 ppm / cm3 even though rust was observed. 2 Detailed analysis of the test materials below revealed that fluorine ions (F - ) and chloride ions (Cl - It was found that the concentration of organic ions detected during the retention time between 100 and 200 s was high. In the case of the coating film in question, for example, decomposition of the resin as a whole is progressing, as in paints with a high content of resins other than fluororesin (such as paints with a blend of fluororesin and acrylic resin), but since the blended amount of fluororesin is small, it was presumed that the apparent amount of eluted fluorine ions was reduced.
[0016] Fluorine ion concentration is 0.1 ppm / cm 2 The test materials that rusted at or below the organic ion concentration were 0.3 ppm / cm 2 and the fluoride ion concentration is 0.1 ppm / cm 2 The test materials that did not show any rust also had only slight elution of organic ions.
[0017] Based on the above findings, the inventors discovered that a method for evaluating the total amount of deteriorated resin, including within the coating film, can be achieved by analyzing eluted ions, which correspond to decomposition products of the resin, thereby making it possible to evaluate the durability over time by focusing on internal deterioration of the coating film, thus arriving at the present invention. That is, the present invention is as follows.
[0018] (1) A method for evaluating the durability of a fluororesin coating against aging deterioration, including not only the surface deterioration of the coating but also the internal deterioration, comprising the steps of: The test material was a steel material coated with a fluororesin-based paint that had been subjected to aging exposure tests in a real environment. 1.0 A hydrogen peroxide solution of 100% by mass was used as the test solution. The coating film in contact with the test solution was irradiated with light having a wavelength of 280 to 380 nm at an irradiation intensity of 80.0w / m 2 24 hours After irradiation, Fluorine ions dissolved in the test solution and organic ions Measure the concentration of The above Converted to unit area of coating each Ion concentration and the correlation between the presence or absence of rust on the test material The durability of the coating film is evaluated using this as an index. A method for evaluating the durability of a coating film. (2) The amount of fluoride ions eluted from the coating is 0.1 ppm / cm 2 and the amount of organic ions eluted is 0.3 ppm / cm 2 In the following, a coating film that shows no rust or undercoat corrosion in the exposure test is rated as a highly durable coating film. The method for evaluating the durability of a coating film according to (1) above. Effect of the Invention
[0019] According to the present invention, it is possible to provide a method for evaluating the long-term durability of a coating film, which reflects the internal deterioration of a fluororesin-based coating film having excellent weather resistance. That is, since the internal deterioration of the coating film is evaluated from the concentration of ions dissolved in a test solution, it is possible to judge the deterioration inside the coating film, which cannot be found only by measuring the surface state such as gloss and color. In addition, by using the method for evaluating the durability of a coating film, it is possible to provide a fluororesin-based coating film having excellent long-term durability performance. [Brief description of the drawings]
[0020] [Figure 1-A] FIG. 1 is a front view illustrating an outline of an apparatus used in a coating durability evaluation method according to the present invention. [Figure 1-B] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] In the method for evaluating the durability of a coating film of the present invention, a region of a specified area (hereinafter referred to as the "contact surface") of a test material on which a coating film has been formed is brought into contact with an aqueous hydrogen peroxide solution, and the contact surface is irradiated with light having a wavelength of 280 to 380 nm at a specified intensity for a specified period of time.The concentration of ions eluted from the contact surface is then measured, and the state of deterioration is judged based on the ion concentration converted into per unit area of the contact surface.
[0022] The area of the contact surface of the test material on which the coating film is formed is not particularly limited, and is preferably 0.8 to 12 cm2, taking into consideration the size of the test material, analytical accuracy, etc. 2 is preferable, and more preferably 5 to 10 cm 2 The contact area is 0.8 cm 2 If the contact area is 12 cm or more, the amount of eluted fluoride ions and organic ions can be secured to a certain extent, and the analysis error can be reduced. 2 If the thickness is equal to or less than this, the light can be irradiated uniformly and the amount of elution required for analysis can be ensured.
[0023] The concentration of hydrogen peroxide used in the evaluation method of the present invention is preferably 0.5 to 2.0 mass%, more preferably 0.7 to 1.8 mass%, and particularly preferably 1.0 to 1.5 mass%. If the concentration of hydrogen peroxide is 0.5 mass% or more, the amount of elution of fluoride ions and organic ions becomes sufficient, and the measurement variation can be reduced. On the other hand, if the concentration is 2.0 mass% or less, there is little risk that the amount of elution of fluoride ions and organic ions will reach a plateau, and discoloration will not occur in a coating film toned with an organic pigment.
[0024] In addition, since there are coating films in which the photodecomposition reaction of the coating film is accelerated by exposure to ultraviolet light, when evaluating such coating films, tests may be performed using only pure water (ion-exchanged water, distilled water, etc.) without using an oxidizing agent such as hydrogen peroxide.
[0025] The light to be irradiated onto the contact surface is light containing ultraviolet rays of 280 nm to 380 nm. When light not containing ultraviolet rays of 380 nm or less or light in the visible light region of 380 nm or more is used, the amount of fluorine ions and organic ions eluted is significantly reduced, making it difficult to evaluate the deterioration state. As the light source, a mercury lamp, a mercury xenon lamp, a dielectric barrier discharge lamp, an LED lamp, etc. can be used.
[0026] The light intensity is 30W / m 2 More than 90W / m 2 Less than 50W / m is preferable. 2 More than 90W / m 2 More preferably, the irradiation intensity is 30 W / m 2 If this is the case, the amount of eluted fluoride ions and organic ions is sufficient for analysis, and the maximum value is 90 W / m 2 If the amount is equal to or less than this, reproducibility will not decrease even if the amount of eluted fluoride ions and organic ions increases.
[0027] The light irradiation time is preferably 6 hours or more and less than 48 hours, more preferably 12 hours or more and less than 36 hours, and even more preferably 20 hours or more and less than 30 hours. If the irradiation time is 6 hours or more, the amount of eluted fluoride ions and organic ions necessary for analysis can be obtained. On the other hand, if the irradiation time is less than 48 hours, the amount of eluted fluoride ions and organic ions will plateau and the reproducibility of data will not deteriorate.
[0028] The coating film to be evaluated in the coating film durability evaluation method of the present invention is a topcoat coating film for outdoor paints, the deterioration of which is accelerated by ultraviolet rays, and is preferably about 25 to 30 μm thick.
[0029] Examples of paints that form coating films to be evaluated include acrylic resin paints, urethane resin paints, epoxy resin paints, modified epoxy resin paints, silicon resin paints, fluororesin paints (polyvinylidene fluoride resin paints, polyvinyl fluoride resin paints, fluororesin paints based on fluoroolefin copolymers, etc.), chlorinated rubber paints, phthalic acid (alkyd) resin paints, etc. The form of these paints is not limited, and may be emulsion paints, water-based paints, solvent paints, powder paints, etc. In the present invention, the term "fluororesin paints" also includes modified fluororesin paints.
[0030] Among these paints, the method for evaluating the durability of a coating film of the present invention is suitable as a method for evaluating the durability of a fluororesin-based paint, which is a durable paint. The fluororesin-based paint may be a mixed paint of a fluororesin and a urethane resin or an acrylic resin.
[0031] Examples of the fluororesin include PTFE (polytetrafluoroethylene), PCTFE (polychlorotrifluoroethylene), PEP (tetrafluoroethylene-hexafluoropropylene copolymer), PVDF' (polyvinylidene fluoride), PVF (polyvinyl fluoride), and FEVE (fluoroethylene-vinyl ether) alternating copolymer.
[0032] The coating durability evaluation method of the present invention is applicable to paints containing titanium oxide. There are no particular limitations on the type, amount, or method of titanium oxide. It is also applicable to paints containing titanium oxide that has been surface-treated to prevent photocatalytic reactions from proceeding, and examples of such paints include paints containing titanium oxide that has been surface-treated with an inorganic component (silica, alumina, etc.) or an organic component (polyol, etc.) and has a titanium oxide content adjusted to 80 to 90% by mass.
[0033] The eluted ions used as an indicator of the deterioration state vary depending on the type of resin that makes up the coating. For fluororesin-based paints, fluorine ions and organic ions are indicators. Also, if the fluororesin contains chlorine in its molecular structure, chlorine ions are also an indicator. On the other hand, for acrylic resin-based paints, urethane resin-based paints, epoxy resin-based paints, and other paints that do not contain fluororesin, organic ions such as carboxylate ions are indicators.
[0034] The ions dissolved in the test solution can be analyzed using an ion chromatograph, etc. The fluorine content, etc. in the test solution can be determined by elemental analysis. EXAMPLES
[0035] Next, the present invention will be described in detail using examples and comparative examples, but the present invention is not limited to only the following examples.
[0036] Example 1 The durability of the coating was evaluated using five types of white paint test materials (A to E) that underwent exposure tests for 10 years in coastal areas. The results of the exposure tests are summarized in Table 1.
[0037] All of the painted test materials were prepared by spray-painting blasted steel with a 50 μm thick undercoat of epoxy resin-based paint and a 25 μm thick topcoat of fluororesin-based paint.
[0038] [Evaluation method] Presence or absence of rust: This was observed visually. Gloss retention: The 60° specular gloss of the coating film before the test was taken as 100%, and the retention rate (gloss retention) (%) of the 60° specular gloss of the coating film after the test was calculated. The 60° specular gloss was measured with a gloss meter.
[0039] [Table 1]
[0040] As shown in Table 1, the gloss retention rate of all test materials exposed for 10 years had decreased to approximately 30%. Test materials A and B showed no signs of rusting and maintained a healthy condition. Test materials C, D, and E showed signs of rusting, although the white topcoat remained. Furthermore, the decrease in film thickness from the beginning of the exposure test was less than 2 μm in all cases, and the initial paint film thickness was maintained.
[0041] Next, for “Test Material C” shown in Table 1, an irradiation test was carried out in an aqueous hydrogen peroxide solution using the cell shown in FIG. That is, on a painted steel plate (test material) 1, an area of 0.7 cm 2 , 7cm 2 Or 15.9 cm 2 A bottom plate 5 (made of glass) having a circular opening was placed with a sealing material 6 interposed therebetween, and a cylindrical glass housing 4 was placed on the bottom plate 5 with a sealing material 6 interposed therebetween. 100 ml of a test solution (aqueous hydrogen peroxide solution) 2 was poured into the housing 4, and then light was irradiated using a light irradiation probe 3.
[0042] For light irradiation, a 200 W highly stable mercury xenon lamp (SUPERCURE-204S (manufactured by SAN-EI ELECTRIC)) with high intensity in the ultraviolet region below 380 nm was used. The position and output of the irradiation probe 3 were adjusted so that the irradiation intensity on the opening of the coated steel plate (test material) 1 in the atmosphere became a predetermined value. The height of the test solution 2 was adjusted by the diameter of the housing 4. The temperature of the test solution 2 was set to 50°C.
[0043] In addition, in Comparative Examples 1-7 in Table 2, which do not use a xenon lamp as a light source, a commercially available solar simulator [entry type] HAL-C100 (note: the spectrum is close to the JIS standard A class solar spectrum) manufactured by Asahi Spectroscopy Co., Ltd. was used.
[0044] [Ion analysis method] After the irradiation test, the concentrations of fluoride ions and organic ions in the hydrogen peroxide solution were measured. The concentration of organic ions was measured by ion chromatography, in which the peak areas of various organic substances detected at retention times between those of fluoride ions and chloride ions were automatically analyzed using Chromeleon 6.80 attached to the ion chromatograph.
[0045] Ion chromatograph: ICS-2100 (manufactured by Thermo Scientific) Column model number: IonPac AS12A Eluent: 2.7 mM sodium carbonate + 0.3 mM sodium bicarbonate
[0046] [Evaluation method] Evaluation 1 is the fluorine ion concentration (ppm / cm) calculated by converting the measurement result of the amount of eluted fluorine ions into a unit area of the opening. 2 ) was recorded. Evaluation 2 is the organic ion concentration (ppm / cm) calculated by converting the measurement result of the amount of eluted organic ions into the organic ion concentration per unit area of the opening. 2 ) was recorded.
[0047] The test results are shown in Table 2.
[0048] [Table 2]
[0049] The test results shown in Table 2 reveal the following: From Examples 1-1 and 1-2 and Comparative Examples 1-1 and 1-2, when the hydrogen peroxide concentration was less than 0.5 mass%, the amount of elution of fluoride ions and organic ions was small even when irradiated with light, and the variation was large. On the other hand, when the hydrogen peroxide concentration exceeded 1.5 mass%, the effect of increasing the amount of elution of fluoride ions and organic ions was saturated.
[0050] From Examples 1-1 and 1-2 and Comparative Examples 1-3 and 1-4, the area of the opening (hereinafter, the contact area) was 0.7 cm 2 Below this, the amount of eluted fluoride ions and organic ions is small, resulting in a large analytical error.2 Above this value, uniform light irradiation becomes difficult, and the concentrations of fluorine ions and organic ions per unit area become smaller.
[0051] From Examples 1-1 and 1-2 and Comparative Examples 1-7, 1-8, and 1-9, it can be seen that, in Examples 1-1 and 1-2, a mercury lamp with a strong irradiation intensity in the range of 280 nm to 380 nm was used as the light source, whereas in Comparative Example 1-7, a light source with a weak irradiation light intensity in the range of 280 nm to 380 nm compared to the visible light region exceeding 380 nm was used, the elution of fluorine ions and organic ions was significantly reduced and quantitative evaluation was not possible. 2 In Comparative Example 1-8, where the irradiation intensity was less than 90 W / m, the elution of fluoride ions and organic ions was significantly reduced. 2 In comparison 1-9, where the elution amount of fluoride ions and organic ions was higher than that of the control, the reproducibility of the elution amount was lower.
[0052] From Examples 1-1 and 1-2 and Comparative Examples 1-5 and 1-6, it is seen that when the irradiation time is less than 6 hours, the elution amount of fluoride ions and organic ions is significantly reduced. On the other hand, when the irradiation time is 48 hours, the elution amount of fluoride ions and organic ions reaches a plateau and the reproducibility of the elution amount is reduced.
[0053] Next, test materials A to E were used to carry out coating film evaluation tests, and the results are shown in Table 3.
[0054] [Evaluation method] The evaluation was performed in the same manner as in Example 1-1, with a hydrogen peroxide concentration of 1.0% by mass and a contact area of 7 cm 2 , irradiation intensity 80W / m 2 The irradiation was carried out under the conditions of 24 hours and 50°C.
[0055] Evaluation 1 is the fluorine ion concentration (ppm / cm) calculated by converting the measurement result of the amount of eluted fluorine ions into a unit area of the opening. 2 ) was recorded. Evaluation 2 is the organic ion concentration (ppm / cm) calculated by converting the measurement result of the amount of eluted organic ions into the organic ion concentration per unit area of the opening. 2 ) was recorded. Evaluation 3 shows the evaluation results of a 10-year exposure test of the corresponding test materials shown in Table 1. The case where no under-film corrosion occurred was marked "O", and the case where rust or under-film corrosion occurred was marked "X".
[0056] [Table 3]
[0057] From Table 3, it can be seen that there was a correlation between the amount of fluoride ions eluted in Evaluation 1 and the amount of organic matter eluted in Evaluation 2, and the occurrence of rust and under-film corrosion in the exposure test in Evaluation 3. In other words, when the amount of both fluoride ions and organic ions eluted was small, no rust or under-film corrosion was observed in the exposure test, whereas when the amount of either fluoride ions or organic ions, or both, eluted was large, rust and under-film corrosion were observed in the exposure test.
[0058] According to the coating durability evaluation method of the present invention, the amount of fluoride ions eluted from the coating is 0.1 ppm / cm 2 The amount of organic ions eluted is 0.3 ppm / cm or less. 2 If it is below this level, it is clear that the fluororesin coating film has excellent durability.
[0059] Example 2 Reference Examples Three types of white fluororesin-based paints (F1 to F3) containing titanium oxide with different properties were spray-painted onto blasted steel, and a 25 μm thick top coat was then applied to the test pieces. Exposure tests were then conducted in coastal areas for 10 years to evaluate the durability of the coating.
[0060] F1: High-grade fluororesin paint containing titanium dioxide that has been highly surface-treated to prevent the paint film from deteriorating. F2: Medium grade fluororesin paint containing moderately surface-treated titanium dioxide. F3: Low-grade fluororesin paint containing titanium dioxide with a low degree of surface treatment
[0061] On the other hand, a durability evaluation test of the coating film was carried out for the three types of coating test materials. In the durability evaluation test, the same device as in Example 1 was used, and the same conditions as in Example 1-1, i.e., hydrogen peroxide concentration 1.0 mass%, opening area 7 cm 2 , 280~380nm wavelength has strong intensity, irradiation intensity 80W / cm 2 The UV irradiation time was set to 24 hours, and the eluted ion concentration was measured after irradiation for 6 hours, 15 hours, and 24 hours.
[0062] The three types of paint, F1, F2, and F3, contain chlorine in the paint resin that makes up the coating, so the concentrations of fluoride ions and chlorine ions eluted from the coating into an aqueous hydrogen peroxide solution were measured.
[0063] The concentration of the eluted ions was measured in the same manner as in Example 1.
[0064] The results of the exposure test and durability test for the coating test materials are shown in Table 4.
[0065] [Table 4]
[0066] From Table 4, it can be seen that in the high-grade fluororesin paint (F1), the amount of fluorine ions eluted was very small even after 24 hours of irradiation. In the medium-grade fluororesin paint (F2), fluorine ions eluted with increasing irradiation time, and the fluorine ion concentration per unit area increased, and in the low-grade fluororesin paint (F3), it was found that fluorine ions eluted even more easily.
[0067] As for chloride ions, it was found that the concentration of eluted chloride ions was low in the high-grade fluororesin paint (F1), while the concentration of eluted chloride ions increased with exposure time in the medium-grade fluororesin paint (F2), and further increased in the low-grade fluororesin paint (F3).
[0068] From Example 2, a correlation was found between the amount of eluted ions and the results of the coating exposure test in fluororesin-based coatings that contain chlorine in the resin structure. In the durability evaluation of fluororesin-based coatings, a correlation was found between the measurement results of fluoride ion concentration and chloride ion concentration, which shows that it is possible to evaluate the inside of the coating by assuming the type of ions eluted from the compounds contained in the coating and measuring the amount of eluted ions using an ion chromatograph or the like.
[0069] According to Example 1 of the present invention, the concentration of fluorine ions dissolved in the test solution after 24 hours of irradiation with light including ultraviolet rays was 0.1 ppm / cm per unit area of the coating test material. 2 The concentration of organic ions dissolved in the test solution is 0.3 ppm / cm per unit area of the coating test material. 2 If the thickness was less than or equal to the thickness, the coating film could be evaluated as having high durability.
[0070] In addition, even in the case of fluorine resin-based paints containing chlorine, the concentration of fluorine ions dissolved in the test solution after 24 hours of irradiation with light containing ultraviolet rays was 0.1 ppm / cm per unit area of the coating test material, as shown in Example 2 of the present invention. 2 The concentration of chloride ions dissolved in the test solution is 0.5 ppm / cm per unit area of the coating test material. 2 If the thickness was less than or equal to the thickness, the coating film could be evaluated as having high durability. [Industrial Applicability]
[0071] The coating durability evaluation method of the present invention can be widely used as a method for judging the quality of the deterioration state inside a coating film, and is particularly effective for diagnosing the life span of coating films on the surfaces of outdoor structures such as steel towers, bridges, power distribution equipment, and buildings, which are prone to internal deterioration due to ultraviolet rays. [Explanation of symbols]
[0072] 1. Painted steel plate (test material) 2. Test solution 3. Light-Illuminating Probe 4. Cabinet 5 Bottom plate (glass) 6 Sealing materials
Claims
1. A method for evaluating the durability of a fluororesin coating against aging deterioration, including not only the surface deterioration of the coating but also the internal deterioration, comprising: The test material was a steel material coated with a fluororesin-based paint that had been subjected to aging exposure tests in a real environment. A 1.0% by mass aqueous hydrogen peroxide solution was used as the test solution. The coating film that had been in contact with the test solution was irradiated with light having a wavelength of 280 to 380 nm at an irradiation intensity of 80.0 W / m 2 for 24 hours, and then Measure the concentrations of fluorine ions and organic ions dissolved in the test solution; The durability of the coating film is evaluated using the correlation between the concentration of each ion converted per unit area of the coating film and the presence or absence of rusting of the test material as an index. A method for evaluating the durability of a coating film.
2. A coating film is evaluated as having high durability if the amount of elution of fluorine ions from the coating film is 0.1 ppm / cm2 or less, the amount of elution of organic ions is 0.3 ppm / cm2 or less, and no rust or corrosion under the coating film is observed in an exposure test. A method for evaluating the durability of a coating film according to claim 1.
Citation Information
Patent Citations
Method for evaluating corrosion resistance of surface of chrome-plated plate
CN110132825A
Device for evaluating and testing durability of painted film metallic product
JP1986210937A
Endurance test method and test device
JP2000097842A
Accelerated exposure testing method and apparatus
JP2001208675A
Weather meter and sample storage box for weather meter
JP2018124086A